Blockade of HLA Antibody-Triggered Classical Complement Activation in Sera From Subjects Dosed With the Anti-C1s Monoclonal Antibody TNT009—Results from a Randomized First-in-Human Phase 1 Trial. Issue 10 (October 2017) - Mühlbacher, Jakob; Jilma, Bernd; Wahrmann, Markus; Bartko, Johann; Eskandary, Farsad; Schörgenhofer, Christian; Schwameis, Michael; Parry, Graham C.; Gilbert, James C.; Panicker, Sandip; Böhmig, Georg A.
Abstract : Background: Complement may play a key role in antibody-mediated rejection. A promising therapeutic approach may be classical pathway (CP) inhibition at the level of early component C1. Methods: In this first-in-human, double-blind, randomized placebo-controlled phase 1 trial, we evaluated the safety and complement inhibitory effect of TNT009, a humanized monoclonal anti-C1s antibody. Sixty-four adult healthy volunteers received either single (n = 48; 7 consecutive cohorts, 0.3-100 mg/kg) or 4 weekly infusions (n = 16; 2 consecutive cohorts, 30 and 60 mg/kg per infusion) of TNT009 or placebo. To assess the effect of treatment on complement activity, sera from dosed subjects were analyzed in a CP activation assay evaluating C3d deposition on HLA-coated microbeads spiked with alloantibodies. Results: Single doses of TNT009 at 3 to 100 mg/kg uniformly and profoundly inhibited HLA antibody-mediated C3d deposition (≥86% after 60 minutes), whereby the duration of CP inhibition (2-14 days) was dose-dependent. Four weekly doses persistently blocked complement for 5 to 6 weeks. Ex vivo serum CP activity was profoundly inhibited when TNT009 concentrations exceeded 20 μg/mL. Infusions were well tolerated without serious or severe adverse events. Conclusions: Treatment with TNT009 was safe and potently inhibited CP activity. Future studies in patients are required to assess the potential of TNT009 for preventing or treating antibody-mediated rejection. Abstract : In a double-blind, randomized, placebo-controlled phase 1 trial in adult healthy volunteers, the authors report that TNT009, an anti-C1s monoclonal antibody, significantly inhibits complement classical pathway activation with an excellent tolerance.